Aurat dan Pakaian Perempuan - Muhammad Mukhtar S.; Mardia Mardia (LPPM IAIN Parepare, 2019)
The issue of nakedness and clothing is a contextual-historical problem. This means that the limits of genitalia and how to dress is a matter of local culture. The development of a culture also influences the conception of values ​​in the actions and interaction patterns of each of its members. Various problems actually arise in society that give rise to pro and contra opinions related to the issue of genitalia and women's clothing, especially the issue of limitation of genitalia on women and the law to close it, clothing or clothing criteria used to cover it. Regarding women's clothing, there are a number of provisions. Firstly, a woman must not reveal her nakedness (large nakedness) except in front of her husband. Secondly, the minimum limitation of women's clothing that generally applies is to close the upper intimate area, namely the breast and underarm area, and cover the lower intimate area. This form of dress is not something that should be treated in social interaction in society, but is demanded to dress in accordance with the ethics, morals, and customs of the community. Thirdly, the Qur'an and Sunnah definitely prohibit all activities, both passive and active, if someone is suspected can cause sexual arousal to the opposite sex. Fourth, QS. An-Nur verses 31 and QS. Al-Ahzab verse 59 is an ethical and moral guidance in dressing for women so that they avoid social disturbances when they leave the house to meet their needs.